2018
DOI: 10.1089/tmj.2017.0088
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychotherapy and the Therapeutic Relationship: Principles, Advantages, and Case Examples

Abstract: Telepsychotherapy offers a novel way to reach and form strong psychotherapeutic relationships with many different types of patients, and it may foster therapeutic intimacy in ways that in-person psychotherapy cannot. More research is needed to further explore this unique modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 17 publications
0
48
0
13
Order By: Relevance
“…For instance, some patients actually report feeling more comfortable and are able to be more open and honest when discussing difficult subjects because of the "protection" or distance afforded by the virtual space of the session. 68,69 Clinicians, too, may feel safer evaluating patients with risk of aggression. 69 As the vignette in Table 1 highlights, rapport can even be established under acute and challenging circumstances.…”
Section: Article Highlightsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, some patients actually report feeling more comfortable and are able to be more open and honest when discussing difficult subjects because of the "protection" or distance afforded by the virtual space of the session. 68,69 Clinicians, too, may feel safer evaluating patients with risk of aggression. 69 As the vignette in Table 1 highlights, rapport can even be established under acute and challenging circumstances.…”
Section: Article Highlightsmentioning
confidence: 99%
“…69,72 Exposure to these advantages may help mitigate clinician's concerns, as successful therapeutic relationships have been established using telepsychiatry across multiple patient populations and psychiatric symptoms. 68,71,[73][74][75][76] COMMUNITY/CULTURAL Telepsychiatry practice often involves challenging culture gaps 16,77 and differences in values. 16,33,38,45,62,67,69,77,78 Psychiatrists from elsewhere may be unfamiliar with local resources and make recommendations for services that are scarce.…”
Section: Article Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Several researchers have also reported that, at a minimum, telebehavioral care is noninferior to in-person behavioral care, [14][15][16] and patients with some behavioral health conditions may even experience improved health outcomes through telebehavioral care compared to in-person care. 17 Access to telebehavioral care has also been reported to reduce the need for inpatient hospitalization. 5 More research is needed regarding temporal, disposition, and cost outcomes for patients with behavioral health diagnoses, who are treated with telehealth in rural EDs to explore any differences in these ED patient outcomes, 6,12 based on different behavioral health diagnoses.…”
mentioning
confidence: 99%